1994
DOI: 10.1152/ajpgi.1994.266.2.g194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prostaglandins on gastrin release from canine antral mucosal cells in primary culture

Abstract: Evidence in vivo indicates that endogenous and exogenous prostaglandins can alter gastrin secretion. We have used primary cultures containing canine antral G-cells to study the cellular actions of prostaglandins on gastrin secretion, comparing the effects of prostaglandin E2 (PGE2) and its synthetic analogue enprostil. Enprostil (10(-10)-10(-6) M) inhibited gastrin secretion in response to bombesin, carbachol, and forskolin, the latter a receptor-independent activator of adenylate cyclase. This inhibition by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
3
1
1
Order By: Relevance
“…However, their observation was in contrast to the report that prostaglandin synthesis inhibition by indomethacin did not influence somatostatin-induced inhibition of either bethanechol-stimulated acid secretion in both conscious and anaesthetized rats (Mogard, Kauffman, Pehlevanian, Golanska, Elashoff & Walsh, 1985), or pentagastrin-stimulated gastric acid and pepsin secretion in conscious cats (Albinus, Gomez-Pan, Hirst & Shaw, 1985). Also, immunoneutralization of somatostatin did not suppress the inhibitory effect of prostaglandin E2 on forskolin-stimulated gastrin release in canine antral mucosal cell culture (Schepp et al 1994), indicating that inhibition by prostaglandin E2 was not mediated by somatostatin. From the present study in conscious rats, it is apparent that both antisomatostatin serum and indomethacin reverse the inhibition by secretin of pentagastrinstimulated acid secretion and both augment basal acid secretion, whereas antisomatostatin serum also augments the pentagastrin-stimulated acid secretion.…”
Section: Discussioncontrasting
confidence: 65%
“…However, their observation was in contrast to the report that prostaglandin synthesis inhibition by indomethacin did not influence somatostatin-induced inhibition of either bethanechol-stimulated acid secretion in both conscious and anaesthetized rats (Mogard, Kauffman, Pehlevanian, Golanska, Elashoff & Walsh, 1985), or pentagastrin-stimulated gastric acid and pepsin secretion in conscious cats (Albinus, Gomez-Pan, Hirst & Shaw, 1985). Also, immunoneutralization of somatostatin did not suppress the inhibitory effect of prostaglandin E2 on forskolin-stimulated gastrin release in canine antral mucosal cell culture (Schepp et al 1994), indicating that inhibition by prostaglandin E2 was not mediated by somatostatin. From the present study in conscious rats, it is apparent that both antisomatostatin serum and indomethacin reverse the inhibition by secretin of pentagastrinstimulated acid secretion and both augment basal acid secretion, whereas antisomatostatin serum also augments the pentagastrin-stimulated acid secretion.…”
Section: Discussioncontrasting
confidence: 65%
“…G cells are stimulated by gastrin-releasing peptide (GRP)/bombesin (1)(2)(3). Sympathomimetics, acetylcholine, prostaglandin, adenosine, and somatostatin are other substances known to act through specific receptors on canine G cells (1,(4)(5)(6)(7). All these receptors belong to the superfamily of seven-transmembrane, G-protein-coupled receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, increased gastric juice gastrin-17 level was observed among patients with HPs and fundic gland polyps. Gastrin has been reported to interact with prostaglandins signaling pathway [30,31] that plays pivotal roles in the mucosal integrity and the normal function of gastrointestinal tract such as the secretion of gastric juice [32][33][34]. The duodenal ulcer is related with reduced PGE2 level [32,34,35]; however, the role of PGE2 in regulating gastric polyps development is unclear.…”
Section: Discussionmentioning
confidence: 99%